2007
DOI: 10.1001/jama.298.12.1429
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamopituitary Dysfunction Following Traumatic Brain Injury and Aneurysmal Subarachnoid Hemorrhage

Abstract: Context Neuroendocrine dysfunction following traumatic brain injury and aneurysmal subarachnoid hemorrhage may occur with a much higher prevalence than previously suspected. This sequela is a potentially serious but treatable complication of brain injury.Objective To review research on hypothalamopituitary dysfunction as an underdiagnosed consequence of traumatic brain injury and subarachnoid hemorrhage, the natural history of this complication, and the potential clinical and public health implications of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
369
5
26

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 472 publications
(431 citation statements)
references
References 60 publications
21
369
5
26
Order By: Relevance
“…In some previous studies, no association of pituitary dysfunction with TBI severity was reported (6,7,(10)(11)(12)(13), whereas others found pituitary dysfunction to be more prevalent in patients with more severe TBI (5,14). In their systematic review, Schneider et al pooled the reported prevalences in severe (35.3%, 95% CI 27.3-44.2%), Mod (10.9%, 95% CI 5.1-21.8%), and MTBI (16.8%, 95% CI 10.9-25.0%) (22), showing that the risk of pituitary dysfunction is higher in patients with STBI than in patients with a MTBI. In order to prevent the underestimation of the prevalence of pituitary dysfunction, our study enrolment procedure implied that the largest effort was made to include patients with Mod/STBI, resulting in an overrepresentation of Mod/STBI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some previous studies, no association of pituitary dysfunction with TBI severity was reported (6,7,(10)(11)(12)(13), whereas others found pituitary dysfunction to be more prevalent in patients with more severe TBI (5,14). In their systematic review, Schneider et al pooled the reported prevalences in severe (35.3%, 95% CI 27.3-44.2%), Mod (10.9%, 95% CI 5.1-21.8%), and MTBI (16.8%, 95% CI 10.9-25.0%) (22), showing that the risk of pituitary dysfunction is higher in patients with STBI than in patients with a MTBI. In order to prevent the underestimation of the prevalence of pituitary dysfunction, our study enrolment procedure implied that the largest effort was made to include patients with Mod/STBI, resulting in an overrepresentation of Mod/STBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hypogonadism may limit fertility, and hypocortisolism and hypothyroidism can be disabling and life-threatening (19,20). Consequently, it was proposed that pituitary function should be screened in all patients after Mod or STBI, even in the absence of symptoms of hypopituitarism (8,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…(76) Next, the luteinizant hormone (LH) and follicular stimulating hormone (FSH) deficiencies are significantly more common than deficiencies of the adrenocorticotropic hormone (ACTH) which are significantly more common than deficiencies of the thyroid stimulating hormone (TSH). (77) The pituitary gland responds to acute traumatic events and many changes in hormone levels become apparent in the first hours or days after trauma. (61,78) Recent studies have shown that various inflammatory mediators including cytokines and free radicals may affect endocrine function at the acute stage of TBI.…”
Section: Neuroendocrine Markersmentioning
confidence: 99%
“…Serum levels of cortisol-binding globulin to cortisol may be decreased in catabolic conditions resulting in disproportionately low total cortisol levels when compared to free cortisol (biologically active). (77,81) Hyperprolactinemia is present in more than 50% of the patients at the acute post-TBI stage. Proof of a negative correlation between prolactine concentrations and TBI severity suggests a good prognostic role for prolactine responses at the acute stage after TBI.…”
Section: Neuroendocrine Markersmentioning
confidence: 99%
See 1 more Smart Citation